ChemInform Abstract: Highly Enantioselective Bromocyclization of Tryptamines and Its Application in the Synthesis of (—)‐Chimonanthine. Issue 20 (20th May 2014) - Xie, Weiqing; Jiang, Guangde; Liu, Huan; Hu, Jiadong; Pan, Xixian; Zhang, Hui; Wan, Xiaolong; Lai, Yisheng; Ma, Dawei
Abstract A highly enantioselective bromocyclization of tryptamine derivatives is developed using a DABCO‐derived bromine complex as bromide source and 8H‐(R)‐TRIP as chiral ligand.